2019
DOI: 10.1039/c8md00457a
|View full text |Cite
|
Sign up to set email alerts
|

Rationally synthesized coumarin based pyrazolines ameliorate carrageenan induced inflammation through COX-2/pro-inflammatory cytokine inhibition

Abstract: In the present work, coumarin based pyrazolines (7a–g) have been synthesized and investigated for their in vitro and in vivo anti-inflammatory potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 60 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…In this context, the present study aims to functionalize the fibrous PCL coating on AZ31 alloy with CM and ZnO nanoparticles. In the last years, coumarins have attracted a great interest due to their wide spectrum of pharmacological properties such as its antibacterial, antitumor, antioxidant and anti-inflammatory activity [ 79 , 80 , 81 ]. A large body of data found in the literature, suggests that CM elicits its anti-inflammatory activity by inhibiting the cyclooxygenase (COX) and lipoxygenase (LOX) pathways of the arachidonic acid metabolism [ 82 , 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the present study aims to functionalize the fibrous PCL coating on AZ31 alloy with CM and ZnO nanoparticles. In the last years, coumarins have attracted a great interest due to their wide spectrum of pharmacological properties such as its antibacterial, antitumor, antioxidant and anti-inflammatory activity [ 79 , 80 , 81 ]. A large body of data found in the literature, suggests that CM elicits its anti-inflammatory activity by inhibiting the cyclooxygenase (COX) and lipoxygenase (LOX) pathways of the arachidonic acid metabolism [ 82 , 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the coatings containing ZnO nanoparticles, namely PCL-ZnO and PCL-CM-ZnO, predominantly showed a small-rounded morphology typical to unstimulated macrophages as noticed in the absence of LPS (TCPS (−)). However, even though the cellular morphology is seen as a characteristic of the inflammatory response towards the biomaterial [ 81 ], recent data revealed that a modified cell morphology does not necessarily indicate a strongly activated macrophage phenotype [ 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite causing several known severe side effects, including cardiovascular, renal, and hepatic disorders, and above all gastrointestinal toxicity, NSAIDs remain the most prescribed drugs in medicine [ 11 , 12 , 13 , 14 , 15 ]. Many of their side effects are due to their mechanisms of action, being associated with inhibition of the enzymes cyclooxygenase (COX) and lipoxygenase (LOX), which directly mediate the production of prostaglandins and leukotrienes, many of which provide protective functions in the body [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…[25] Similarly, coumarin-based pyrazolines were evaluated for anti-inflammatory activity. [26] Also, coumarin-based pyrans possess molecular switching properties. [27] Without a doubt, heterocycles fused with coumarin/pyrrole may also display intriguing functional properties.…”
Section: Introductionmentioning
confidence: 99%